"Natural" virtuosos: Paradoxical polysemy and the rhetoric of the Fisk Jubilee Singers. Issue 3 (3rd July 2022) - Jakes, Kelly
ABSTRACT: This article examines the rhetoric of the Fisk Jubilee Singers, the famous nineteenth-century choir whose domestic and international performances saved Fisk University from financial ruin, legitimized African American spirituals as high art, and offered a powerful argument for Black American citizenship during the post-Reconstruction era. While scholars have examined reactions to the choir's performances in the nineteenthcentury press, none have studied the organization's own discourse for insights into how the choir's white leaders positioned and promoted the troupe. In this essay, I recover their discourse by examining 35 extant concert programs that accompanied the Singers' performances between 1871 and 1878. I argue that they work through a rhetorical move that I have termed paradoxical polysemy, a type of polysemy that emerges in contexts beset by ambivalence and navigates multiple, contradictory beliefs within a singular audience. Deploying appeals to the choir's "natural" musical talent that worked in two different registers, the programs negotiated white allies' inconsistent beliefs about race, appealing both to their desire to help Black people and their wish to maintain white supremacy. Additionally, these dual appeals to the "natural" worked to help the Singers argue for the political and social inclusion of all Black Americans, regardless of their level of education.